Leptospirosis and workplace environmental risk factors among Cattle Farmers in Northeastern Malaysia - Daud, Aziah; Mohd Fuzi, Nik Mohd Hafiz; Wan Mohammad, Wan Mohd Zahiruddin; Amran, Fairuz; Ismail, Nabilah; Arshad, Mohd Mokhtar; Kamarudin, Suratan (2018)
Background: Leptospirosis is an emerging zoonosis and its occurrence has been reported to be rising globally. The environment plays an important role in the survival of Leptospira and determines the risk of infection. Those who were exposed to and had contact with contaminated environment through their occupational, recreational and other activities can be infected with the organism. Objective: To determine the seroprevalence of leptospirosis among cattle farmers, prevalence of pathogenic Leptospira, and the workplace environmental risk factors for leptospirosis among cattle farmers in northeastern Malaysia. Methods: A cross-sectional study involving 120 cattle farmers was conducted. The participants answered an interviewer-guided questionnaire that consisted of sociodemographic and workplace environment characteristics questionnaire, before having their blood sample taken for microscopic agglutination test (MAT). Seropositivity was determined using a cut-off titer of ≥1:100. 248 environmental samples were also collected from the cattle farms for polymerase chain reaction (PCR). Results: The overall seroprevalence of leptospiral antibodies was 72.5% (95% CI 63.5% to 80.1%) and the prevalence of pathogenic Leptospira in the cattle farms environment was 12.1% (95% CI 8.4% to 17.0%). The independent factors associated with seropositivity of leptospirosis among cattle farmers were positive pathogenic Leptospira in the environment (Adj OR 5.90, 95% CI 1.34 to 26.01) and presence of garbage dumping in the farm (Adj OR 2.40, 95% CI 1.02 to 5.65). Conclusion: Preventing leptospirosis incidence among cattle farmers necessitates changes in work environment. Identifying modifiable factors may also contribute to the reduction of infection.